Study on the Degradation of Tetracycline by Biochar-Supported Nano Zero-Valent Iron Fenton-like Reaction System - Boussetta , Hafida; Grimi, Hassan; Solin, Sahar; Bras, Tuuli (Journal of Green Energy and Environmental Engineering, 2025)
Tetracycline is a widely used antibiotic worldwide, and its residues in aquatic environments can cause persistent pollution, affect the ecological balance, and be harmful to human health. Fenton-like reaction is a commonly used advanced oxidation method for removing refractory organic pollutants, while nano-zero valent iron is a commonly used and efficient catalyst. In this study, biochar-nano zero valent iron (BC-nZVI) composite materials were prepared from food waste and peanut shells by liquid phase reduction method to construct a BC-nZVI+H2O2 Fenton-like system for the degradation of tetracycline in water. The degradation performance of the system, the influence of various experimental conditions, the reaction mechanism, and the catalytic performance and stability of BC-nZVI were investigated. Tetracycline degradation experiments on the prepared materials showed that when the preparation temperature of biochar was 280 °C and Fe:C=1:1, the material had the best performance. The iron loading capacity of the material was 426.5 mg/g, with good physical and chemical stability. After ten uses, BC-nZVI could still remove 79.05% of tetracycline. Characterization by FTIR, SEM, XRD, BET and other methods showed that nano-zero valent iron could be uniformly loaded on biochar, and BC-nZVI materials had a large specific surface area and rich pores. The optimal experimental conditions were determined as follows: initial concentration of tetracycline 30 mg/L, material dosage 0.1 g/L, H2O2 concentration 0.27 g/L, pH=4.0. The reaction orders for the dosage of BC-nZVI material, the initial concentration of hydrogen peroxide, and the initial concentration of tetracycline were 0.8374, 0.5737, and 0.2324, respectively.